Land Use and Soil Management Effects on Infiltration Model Parameters in Semi-arid Tropical Alfisols - Ramesh, V; Bandyopadhyay, K K; Sharma, K L; Wani, S P (Annals of Arid Zone, 2016)
Soil infiltration parameters for empirical and process-based models were evaluated in different land use systems, namely agriculture (farmers' and high management systems) and permanent fallow management system in tw0 typical benchmark sites of Alfisol series (Hayathnagar and 'Kasireddipally) in Andhra Pradesh. Under permanent fallow, the soil series of Kasireddipally had four times higher steady state infiltration rate as compared to that in agricultural systems due to better soil physico-chemical properties. Among the agricultural systems, the steady state infiltration rate was higher by 78%under high management than in the farmers' management. Initial infiltration rate (B) and change in infiltration rate with time (n) in the permanent fallow and high management levels were considerably different than under agriculture and farmers' management. The different parameters of Horton model, io (the initial infiltration) and k (constant that determines the rate at which initial infiltration rate reaches steady state infiltration) were found to be higher in the permanent fallow as compared to agricultural land use. High management levels had beneficial influence on soil infiltration. Based on the coefficient of determination (R2), percentage error (PE), coefficient of residual mass (CRM) and model efficiency (ME) parameters, the Horton's model gave the best representation of infiltration rate and time relationship in Alfisols. Key words: Alfisol, infiltration, models, semi-arid tropics, land use management system.